Beyond Class Activities to Involve Women. Fab Lab-Based Learning in Latin America - Herrera, Pablo C. (2024)
This quantitative research analyzes the participation of Latin American women graduates in a Fab Lab-based learning environment in the IEEE Region 9, including 176 graduates from 11 countries between 2012 to 2023. We analyzed 20% (N=36) of Women graduates in Latin America in 24 of 303 Fab Labs, and we compared them with 361 Fab Academy graduates from countries of other nine IEEE regions. The results reveal differences, which indicate a lower number of graduates in the Andean sub-region compared to countries of the extreme south of America. This includes only 17% of Women managing a Fab Lab. Latin America demonstrates the lowest percentage of Women graduates and managers compared to other IEEE regions. This longitudinal analysis highlights for future research, beyond the academic issues that contribute to the reduction of the gender gap.